1997
DOI: 10.1007/s001250050810
|View full text |Cite
|
Sign up to set email alerts
|

Protein intake and urinary albumin excretion rates in the EURODIAB IDDM Complications Study

Abstract: Kidney disease is a common and costly complication [1,2] of diabetes mellitus, with individuals often requiring dialysis or renal transplantation. More than 30 % of people with insulin-dependent diabetes mellitus (IDDM) are at risk of manifest renal disease [3][4][5]. In the EURODIAB IDDM Complications Study 30.6 % of a stratified European sample of individuals with IDDM aged 15-60 years (mean diabetes duration: 15 years) had albumin excretion rates (AER) of 20 m g/min or higher. In persons with a diabetes dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 50 publications
3
37
1
5
Order By: Relevance
“…The safety of these agents have been questioned, for example, saccharin as a risk factor for bladder cancer, and aspartame in precipitating seizures, producing hyperactivity and other behavioural problems in children (Walton et al, 1993) and altering mood in susceptible patients (Renwick, 1993). Well designed studies have not supported any of these claims (Tollefson et al, 1992;Toeller et al, 1997).…”
Section: Non-nutritive Sweetenersmentioning
confidence: 99%
“…The safety of these agents have been questioned, for example, saccharin as a risk factor for bladder cancer, and aspartame in precipitating seizures, producing hyperactivity and other behavioural problems in children (Walton et al, 1993) and altering mood in susceptible patients (Renwick, 1993). Well designed studies have not supported any of these claims (Tollefson et al, 1992;Toeller et al, 1997).…”
Section: Non-nutritive Sweetenersmentioning
confidence: 99%
“…Of the thirteen studies that reported an association between protein and nephropathy there were three cross-sectional studies (Toeller M et al 1997;Riley MD& Dwyer T 1998;O'Hayon BE et al 2000), one case control study (Möllsten AV et al 2001), two cohort studies (Jibani MM et al 1991;Barsotti G et al 1998), six randomized controlled trials (Brouhard BH& LaGrone L 1990;Zeller K et al 1991;Dullaart RP et al 1993;Raal FJ et al 1994;Hansen HP et al 1999;Hansen HP et al 2002) and a pilot study (Percheron C et al 1995). These will be discussed in the following paragraphs by study design.…”
Section: Macronutrients 211 Proteinmentioning
confidence: 99%
“…Patients are pleased to hear that, while making healthy choices, the end result is the freedom to eat what they like, when they like. 7 Should clinicians require patients to fail twice-daily injections of premixed insulin before offering the preferred therapy, basal-prandial-correction therapy? To some extent, the answer is determined by patient preference.…”
Section: Commentarymentioning
confidence: 99%
“…Researchers concluded that people with diabetes should not exceed a protein intake of 20% of calories. 7 Any study in type 1 diabetes is applicable to type 2 diabetes as it relates to nephropathy. Therefore, there is evidence to recommend avoidance of high protein intakes in patients at risk for renal disease, i.e.…”
Section: A S E S T U D I E Smentioning
confidence: 99%